2004
DOI: 10.1002/bdra.10136
|View full text |Cite
|
Sign up to set email alerts
|

Developmental toxicity of arecoline, the major alkaloid in betel nuts, in zebrafish embryos

Abstract: Arecoline-treated embryos exhibited general developmental retardation in a dose-dependent manner. Our results from RT-PCR, in situ hybridization, and antioxidant-protection experiments indicate that the mechanism underlying growth retardation by arecoline in embryos is predominantly due to a general cytotoxic effect induced by depletion of intracellular thiols.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 54 publications
1
21
1
Order By: Relevance
“…Arecoline-treated embryos exhibited general developmental retardation. By using RT-PCR, in situ hybridization, and antioxidant-protection experiments, Chang et al (2004) indicated that the mechanism underlying growth retardation by arecoline in embryos is predominately due to a general cytotoxic effect induced by depletion of intracellular thiols. Besides, a study by Hung et al (2011) demonstrated that, in human umbilical vein endothelial cells (HUVECs), arecoline stimulated the production of ROS and expressions of ICAM and VCAM.…”
Section: Toxicologymentioning
confidence: 99%
“…Arecoline-treated embryos exhibited general developmental retardation. By using RT-PCR, in situ hybridization, and antioxidant-protection experiments, Chang et al (2004) indicated that the mechanism underlying growth retardation by arecoline in embryos is predominately due to a general cytotoxic effect induced by depletion of intracellular thiols. Besides, a study by Hung et al (2011) demonstrated that, in human umbilical vein endothelial cells (HUVECs), arecoline stimulated the production of ROS and expressions of ICAM and VCAM.…”
Section: Toxicologymentioning
confidence: 99%
“…1, 2, 2628 This discrepancy can be due to the analyses of raw areca nut in earlier studies and the fact that the total amount and composition of alkaloids varies with the age of areca fruit. For instance, arecoline levels in the nut rise during the maturation period but drop significantly in the matured nut.…”
Section: Resultsmentioning
confidence: 97%
“…Currently, the zebrafish embryo model is being utilized extensively (e.g., Oberemm et al, 1997;Papendorf et al, 1997;Chang et al, 2004;Lefebvre et al, 2004;see Teraoka et al, 2003) to identify developmental toxicity of sublethal doses of naturally occurring toxins. However, in this case, although lower concentrations of the pahayokolide A produced lower numbers of dead embryos, no specific or consistent effect on embryo development, such as morphological malformation or apparent dysfunction of developmental processes, were observed.…”
Section: Discussionmentioning
confidence: 99%